Biodegradation of plasticiser di-n-butyl phthalate by immobilised microbial cells - Wu, Weizhong; Meng, Xianlin (INTERNATIONAL JOURNAL OF ENVIRONMENT AND POLLUTION, 2009)
Microorganisms capable of degrading Di-n-Butyl Phthalate (DBP) were isolated by acclimation and enrichment techniques. The adaptation of microorganisms to DBP was investigated. The microbial cells were immobilised onto the ceramic honeycomb supports. The DBP degradation was performed in a novel kind of bioreactor using ceramic honeycomb support as carrier for microbial immobilisation. The experimental results showed that the biomass adsorbed onto the ceramic support could reach 95 mg dry weight/g carrier. The immobilised microbial cells were used for the treatment of wastewater containing DBP. The results demonstrated that the DBP concentration of the outlet reached the stationery-state level of less than 1.0 mg/L within three days at inlet DBP concentration of 100 mg/L and 12 h of hydraulic retention time.